DRAMA TARI TOPENG BONDRES SEBAGAI MEDIA PENERANGAN HINDU - Parmajaya I Putu Gede (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2017)
Mask Bondres whose development began in the nineties did get its own place for the people of Bali. Displays the dance plays that are unit and not tied to a grip of dance or storyline. Mask performing art displays funny figures, with fresh humor sometimes inserted social satire or  confessional  ailments that  occur in  society.  But  sometimes it  also  conveys  moral  ethical messages  by  taking  philosophies  or  pitutur-pitutur  originating  from  Hindu  Religion  in particular.Topeng Bondres is unique in which combine dance, drama and gamelan art. In addition to displaying funny figures, with fresh humor sometimes in selipi satire of social idiosyncrasies or konilik that occurred in the community. But sometimes also convey moral ethical messages by taking philosophy-philosophy or pitutur-originated from Hindu Religion in particular.Keywords: Dance, Bondres, Media